EFEKTIVITAS PENGGUNAAN MODELPEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI PONPES AL-MUKHTARIYYAH SUNGAI DUA - Ria lestari Harahap; Yulia Pratiwi Siregar; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2020)
Abstract This study aims to know whether there is a significant effectiveness of using Think Pair Share (TPS) learning model on students’ mathematical problem solving ability on the topic of solid at the eighth grade students of Ponpes Al-Mukhtariyyah Sungai Dua Portibi. The research was conducted by applying experimental method (one group pretest post test design) with 42 students as the sample and they were taken by using simple random sampling technique from 128 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using TPS learning model was 3,33 (very good category) and (b) the average of students’ mathematical problem solving ability on the topic of solid before using TPS learning model was 61.65 (enough category) and after using TPS learning model was 79.66 (good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 20),the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant effectiveness of using Think Pair Share (TPS) learning model on students’ mathematical problem solving ability on the topic of solid at the eighth grade students of Ponpes Al-Mukhtariyyah Sungai Dua Portibi. Keywords: TPS learning model, on students’ mathematical problem solving ability